RETRACTED: The Effect of Career Development, Work Professionalism, Work Motivation, and Interpersonal Communication on Employee Performance in Hospitals. Metropolitan Medical Centre South Jakarta - Dewi Mardayani; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aims to determine the effect of Career Development, Work Professionalism, Work Motivation, and Intepersonal Communication to the Perormance of Eployee at RS. Metropolitan Medical Centre South Jakarta. The data of this study used primary data in the form of questionnaires to 85 employees of RS. Metropolitan Medical Centre South Jakarta. Data analysis techniques using multiple linear regression analysis and using the program SPSS 24.00. The results showed an influence between Career Development (X1), Employee Performance (Y) of 0,295 and an influence of 29,5%. Similarly, the variable Work Professionalisme(X2) on Employee Performance (Y) of 0,294 and has an influence of 29,4%. Then for the variable Work Motivation (X3) on Employee Performance (Y) of 0,158 and has an influence of 15,8%. Then on variables Interpersonal Communication on Employee Performance (Y) of 01,23 and has an influence of 12,3%. Partially or simultaneously have a strong influence among the three variables, the most significant is the Career Development of 0,000.